Effects of Tobacco Use on the Macrostructure and Microstructure of Sleep in Patients with OSA - Ji W; Shi L; Ji Z; Zhao Z; Lin L; Wang X; Cheng J; Chen X (Nature and Science of Sleep)
Wei Ji,1,* Liyong Shi,1,2,* Zhiqiang Ji,3,* Zhihuang Zhao,1 Lianshun Lin,1,2 Xiali Wang,4 Jing Cheng,4 Xiaoyang Chen1,2 1The Second Clinical College of Fujian Medical University, Quanzhou, Fujian Province, 362000, People’s Republic of China; 2Department of Pulmonary and Critical Care Medicine, The Second Affiliated Hospital of Fujian Medical University, Quanzhou, Fujian Province, 362000, People’s Republic of China; 3Zunyi Medical University, Zunyi, Guizhou Province, 563006, People’s Republic of China; 4Quanzhou Medical College, Quanzhou, Fujian Province, 362000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoyang Chen, Email ccxxyy008@fjmu.edu.cnObjective: Both tobacco use and obstructive apnea-hypopnea syndrome (OSA) can affect sleep, and it is speculated that tobacco use may further affect the sleep of those with OSA. Our primary objective is to clarify the associations between tobacco use and the macrostructure and microstructure of sleep in patients with OSA.Methods: This retrospective study encompasses a cohort of 1017 patients who were hospitalized between January 2020 and January 2023 for the investigation of sleep disorders. Rigorous inclusion criteria were applied, and all patients underwent a comprehensive polysomnography (PSG) assessment and completed a Pittsburgh Sleep Quality Index (PSQI) questionnaire.Results: Patients with OSA who concurrently used tobacco exhibited markedly inferior sleep quality than those who did not. Notably, there was no association between the degree of tobacco dependence and sleep quality. Those with OSA who used tobacco demonstrated a significant prolongation of stage 1 light sleep and a reduction of deep sleep duration (N3). In this group, those who demonstrated poor sleep quality had more pronounced alterations in light sleep stages with prolonged N1 and shortened N2 stages.Conclusion: Our findings reveal a substantial reduction in sleep quality amongst OSA patients who also use tobacco, compared to those with OSA who do not use tobacco. The rate of poor sleep quality was not linearly associated with the level of tobacco dependence. Tobacco use was associated with alterations in both light and slow wave sleep in those with OSA. Importantly, the effects of tobacco dependence on sleep structure were more pronounced in those with more severe OSA.Keywords: tobacco, sleep structure, sleep quality, OSA